High Arctic Large Igneous Province Alkaline Rocks in Canada: Evidence for Multiple Mantle Components. (9th June 2021) - Bédard, Jean H; Troll, Valentin R; Deegan, Frances M; Tegner, Christian; Saumur, Benoit M; Evenchick, Carol A; Grasby, Stephen E; Dewing, Keith
Abstract: The Cretaceous High Arctic Large Igneous Province (HALIP) in Canada, although dominated by tholeiites (135–90 Ma), contains two main groups of alkaline igneous rocks. The older alkaline rocks (∼96 Ma) scatter around major fault and basement structures. They are represented by the newly defined Fulmar Suite alkaline basalt dykes and sills, and include Hassel Formation volcanic rocks. The younger alkaline group is represented by the Wootton Intrusive Complex (92·2–92·7 Ma), and the Audhild Bay Suite (83–73 Ma), both emplaced near the northern coast of Ellesmere Island. Fulmar Suite rocks resemble EM-type ocean island basalts (OIB) and most show limited crustal contamination. The Fulmar Suite shows increases of P2 O5 at near-constant Ba–K–Zr–Ti that are nearly orthogonal to predicted fractionation- or melting-related variations, which we interpret as the result of melting composite mantle sources containing a regionally widespread apatite-bearing enriched component (P1). Low-P2 O5 Fulmar Suite variants overlap compositionally with enriched HALIP tholeiites, and fall on common garnet lherzolite trace element melting trajectories, suggesting variable degrees of melting of a geochemically similar source. High-P2 O5 Hassel Formation basalts are unusual among Fulmar rocks, because they are strongly contaminated with depleted lower crust; and because they involve a high-P2 O5 –Ba–Eu mantle component (P2), similar to that seen in alkali basalt dykes from Greenland. The P2 component may have contained Ba–Eu-rich hawthorneite and/or carbonate minerals as well as apatite, and may typify parts of the Greenlandic sub-continental lithospheric mantle (SCLM). Mafic alkaline Audhild Bay Suite (ABS) rocks are volcanic and hypabyssal basanites, alkaline basalts and trachy-andesites, and resemble HIMU ocean island basalts in having high Nb, low Zr/Nb and low 87 Sr/ 86 Sri . These mafic alkaline rocks are associated with felsic alkaline lavas and syenitic intrusions, but crustally derived rhyodacites and rhyolites also exist. The Wootton Intrusive Complex (WIC) contains geochemically similar plutonic rocks (alkali gabbros, diorites and anatectic granites), and may represent a more deeply eroded, slightly older equivalent of the ABS. Low-P2 O5 ABS and WIC alkaline mafic rocks have flat heavy rare earth element (HREE) profiles suggesting shallow mantle melting; whereas High-P2 O5 variants have steep HREE profiles indicating deeper separation from garnet-bearing residues. Some High-P2 O5 mafic ABS rocks seem to contain the P1 and P2 components identified in Fulmar–Hassel rocks, whereas other samples trend towards possible High-P2 O5 + Zr (PZr) and High-P2 O5 + K2 O (PK) components. We argue that the strongly alkaline northern Ellesmere Island magmas sampled mineralogically heterogeneous veins or metasomes in Greenlandic-type SCLM, which contained trace phases such as apatite, carbonates, hawthorneite, zircon, mica or richterite. The geographically more widespread apatite-bearing component (P1) could have formed part of a heterogeneous plume or upwelling mantle current that also generated HALIP tholeiites when melted more extensively, but may also have resided in the SCLM as relics of older events. Rare HALIP alkaline rocks with high K–Rb–U–Th fall on mixing paths implying strong local contamination from either Sverdrup Basin sedimentary rocks or granitic upper crust. However, the scarcity of potassic alkaline HALIP facies, together with the other trace element and isotopic signatures, provides little support for a ubiquitous fossil sedimentary subduction-zone component in the HALIP mantle source.